Challenges and opportunities in the recovery of gold from electronic waste - Rao M.D.; Singh K.K.; Morrison C.A.; Love J.B. (My University, 2025)
Rapid global technological development has led to the rising production of electronic waste that presents both challenges and opportunities in its recycling. In this review, we highlight the value of metal resources in the printed circuit boards (PCBs) commonly found in end-of-life electronics, the differences between primary (ore) mining applications and secondary ('urban') mining, and the variety of metallurgical separations, in particular those that have the potential to selectively and sustainably recover gold from waste PCBs. © 2020 The Royal Society of Chemistry.